DMFT (Decayed, Missing, Filled, Teeth) Oral Health Index in Sweets and Cable Industry Workers - Z Tohidast akrad; JM Beitollahi; AA Khajetorab (Tehran University of Medical Sciences, 2006)
The most important factor in evaluating dental health is DMFT (Decayed, Missing, Filled, Teeth). This research was conducted to compare DMFT index in the workers of sweets and cable factories of Shahrood (Moghan), a small city near 300 km east of Tehran. All the 127 production line workers of cable factory and 124 workers of sweets factory who had the predetermined criteria were selected. A questionnaire was filled out and dental status was recorded for each one. After analyzing the data by SPSS soft ware the results were as follows: Mean and SD of DMFT in sweets factory: 12.59± 6.5; in cable factory: 9.7± 5.4; and Caries free in both factories was less than 1% which was neglectable. Mean and SD of DMFT in 35- 44 yr age group in sweet and cable factory was 11.6± 6.05, and 10.8± 6.5, respectively. With Anova two-way analysis in two groups and with P< 0/000, there was a significant correlation between type of work and DMFT which proved the hypothesis. Accordingly, consumption of sweets and neglecting oral hygiene can be considered of great importance in increasing DMFT in the workers of sweets factory compared to the cable factory.